101 law forms for personal use - Nolo (Firm) (Berkeley, California : Nolo, 2020)
Get it in writing with Nolo's 101 Law Forms for Personal Use. Covering everything from promissory notes to planning an estate, this comprehensive collection of ready-to-use documents helps you protect your legal rights and avoid costly disputes.
Delegating authority to care for children, pets, and property -- Basic estate planning -- Things to do after a death : documents for executors -- Renting a place to live -- Borrowing and lending money -- Buying a house -- Buying or selling a car, dog, or other personal property -- Renting personal property and storing goods -- Home repairs and maintenance -- Handling personal finances -- Dealing with junk mail and telemarketing calls -- Hiring child care, elder care, or household help -- Living together -- Settling legal disputes -- Miscellaneous forms for personal use.
Includes index.
110601
Keywords: Forms (Law) -- United States -- Popular works; Popular works; Law for laypersons